2015
DOI: 10.7306/gq.1216
|View full text |Cite
|
Sign up to set email alerts
|

The use of FPXRF in the determinations of selected trace elements in historic mining soils in the Holy Cross Mts., south-central Poland

Abstract: Migaszewski, Z.M., Ga³uszka, A., Do³êgowska, S., 2015. The use of FPXRF in the de ter mi na tions of se lected trace el e ments in his toric min ing soils in the Holy Cross Mts., south-cen tral Po land. Geo log i cal Quar terly, 59 (2): 248-256, doi: 10.7306/gq.1216 In this study, con cen tra tions of As, Cu, Mn, Pb, and Zn were de ter mined in 231 sam ples of mine soils and spoils by field porta ble X-ray flu o res cence (FPXRF), and by in duc tively cou pled plasma-mass spec trom e try (ICP-MS) as a com … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Results of this study share a number of similarities with the findings of Migaszewski and Gałuszka (2008) who attempted to describe the specific properties of the subhorizon-Ofh, and the possibility of its use in geoindicative studies, especially in relation to Cd, Hg and Pb. The experimental work carried out within three Polish national parks, with the use of various soil horizons and subhorizons (Ol, Ofh, AE, ABC, BC, B, C, R), showed that the subhorizon-Ofh is enriched in the above-mentioned elements compared with the lower soil horizons (Migaszewski et al, 2002(Migaszewski et al, , 2004(Migaszewski et al, , 2005. The authors hypothesised that this subhorizon could be a potential geoindicator of temperate soil quality and our results seem to confirm this hypothesis in relation to Hg, Cd and Zn.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Results of this study share a number of similarities with the findings of Migaszewski and Gałuszka (2008) who attempted to describe the specific properties of the subhorizon-Ofh, and the possibility of its use in geoindicative studies, especially in relation to Cd, Hg and Pb. The experimental work carried out within three Polish national parks, with the use of various soil horizons and subhorizons (Ol, Ofh, AE, ABC, BC, B, C, R), showed that the subhorizon-Ofh is enriched in the above-mentioned elements compared with the lower soil horizons (Migaszewski et al, 2002(Migaszewski et al, , 2004(Migaszewski et al, , 2005. The authors hypothesised that this subhorizon could be a potential geoindicator of temperate soil quality and our results seem to confirm this hypothesis in relation to Hg, Cd and Zn.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Other studies of Spolic Technosols in Poland in recent years included studies of geochemistry and mineralogy of technogenic soils developed on old mine heaps of abandoned iron ore mines (Swęd and Niedzielski, 2018), as well as determination of geochemical background in soils in the vicinity of abandoned pyrite-uranium, copper, and zinc-lead mines (Gałuszka et al, 2015(Gałuszka et al, , 2016(Gałuszka et al, , 2018Migaszewski et al, 2015).…”
Section: Technogenic Soils In Industrial and Mining Areasmentioning
confidence: 99%
“…Radu assessed the reliability of FPXRF by AAS [22], whereas some other scholars also used ICP-MS [21,[31][32][33][34] and ICP-AES [35][36][37] to conduct comparison with FPXRF.…”
Section: Correlation and Linear Regression Analysismentioning
confidence: 99%